Toward Universal Coverage : Turkey’s Green Card Program for the Poor - Menon, Rekha; Mollahaliloglu, Salih; Postolovska, Iryna (World Bank, Washington DC, 2013)
This case study unravels Turkey's path to universal coverage. It outlines both the transformation of the health system and the performance of the 'Yesil Kart', the Green Card, program, a noncontributory health insurance scheme for the poor. Initially launched in 1992, the Green Card program has seen a rapid expansion in the number of beneficiaries and program benefits since the implementation of the Health Transformation Program, or HTP in 2003, with the number of beneficiaries more than tripling, from 2.5 million beneficiaries in 2003 to 9.1 million beneficiaries in 2011. In addition, both the coverage and targeting of the program improved substantially. While the Green Card program initially began as a separate targeted scheme for the poor, in January 2012 it became part of the UHI scheme managed by Social Security Institution, or SSI. As this study will show, gradual steps were taken over the years to expand coverage, improve targeting, and expand benefits of the Green Card program to align it with the UHI. This, combined with the improvements in service delivery within a comprehensive reform of the health sector, makes Turkey a unique example of universal coverage for quality health services. The study is organized as follows. Section two briefly outlines Turkey's health reform and how health care is currently organized and delivered. Section three describes the Green Card Program, it evolution, and its performance. The final section discusses the pending agenda.